Modulation of individual auditory-motor coordination dynamics through interpersonal visual coupling. Issue 1 (December 2017) - Miyata, Kohei; Varlet, Manuel; Miura, Akito; Kudo, Kazutoshi; Keller, Peter
Abstract The current study investigated whether visual coupling between two people producing dance-related movements (requiring whole-body auditory-motor coordination) results in interpersonal entrainment and modulates individual auditory-motor coordination dynamics. Paired participants performed two kinds of coordination tasks – either knee flexion or extension repeatedly with metronome beats (Flexion-on-the-beat and Extension-on-the-beat conditions) while standing face-to-face or back-to-back to manipulate visual interaction. The results indicated that the relative phases between paired participants' movements were closer to 0° and less variable when participants could see each other. In addition, visibility of the partner reduced individual differences in the dynamics of auditory-motor coordination by modulating coordination variability and the frequency of phase transitions from Extension-on-the-beat to Flexion-on-the-beat. Together, these results indicate that visual coupling takes place when paired participants can see each other and leads to interpersonal entrainment during rhythmic auditory-motor coordination, which compensates for individual differences via behavioural assimilation and thus enables individuals to achieve unified and cohesive performances.